A long ncRNA links copy number variation to a polycomb/trithorax epigenetic switch in FSHD muscular dystrophy - Cabianca, Daphne S; Casa, Valentina; Bodega, Beatrice; Xynos, Alexandros; Ginelli, Enrico; Tanaka, Yujiro; Gabellini, Davide (Cell, 2012)
Repetitive sequences account for more than 50% of the human genome. Facioscapulohumeral muscular dystrophy (FSHD) is an autosomal-dominant disease associated with reduction in the copy number of the D4Z4 repeat mapping to 4q35. By an unknown mechanism, D4Z4 deletion causes an epigenetic switch leading to de-repression of 4q35 genes. Here we show that the Polycomb group of epigenetic repressors targets D4Z4 in healthy subjects and that D4Z4 deletion is associated with reduced Polycomb silencing in FSHD patients. We identify DBE-T, a chromatin-associated noncoding RNA produced selectively in FSHD patients that coordinates de-repression of 4q35 genes. DBE-T recruits the Trithorax group protein Ash1L to the FSHD locus, driving histone H3 lysine 36 dimethylation, chromatin remodeling, and 4q35 gene transcription. This study provides insights into the biological function of repetitive sequences in regulating gene expression and shows how mutations of such elements can influence the progression of a human genetic disease.